Introduction to special issue Kanapoi: Paleobiology of a Pliocene site in Kenya. Issue 140 (March 2020) - Manthi, Fredrick K.; Plavcan, J. Michael; Ward, Carol V.
Abstract: This paper introduces this Special Issue of the Journal of Human Evolution entitled "Kanapoi: Paleobiology of a Pliocene site in Kenya." Kanapoi, West Turkana, Kenya, is part of the Omo-Turkana Basin and is the type site of the earliest known genus of Australopithecus, A. anamensis . Kanapoi preserves among the earliest earliest evidence of Australopithecus in deposits dated between 4.195 to 4.108 million years old. Explored by several teams since the 1960s, the Kanapoi sediments have yielded a rich and abundant fauna, providing important information about the paleoenvironments and the context surrounding the earliest evolution of the genus Australopithecus, as well as about the evolution and biogeography of African Pliocene vertebrate faunas.